Penerapan Arsitektur Ramah Lingkungan pada Kawasan Peternakan Modern di Kota Makassar - Abduh, Zul; Said, Ratriana; Alfiah, Alfiah (TIMPALAJA : Architecture Student Journals, 2024)
This study aims to develop a bioclimatic design framework for the Pantai Alam Aquatic Center in Bulukumba Regency, Indonesia, tailored to the local humid climate. Bioclimatic architecture, which integrates climatic data and environmental considerations into building design, is employed to enhance energy efficiency and user comfort. This design includes the use of natural ventilation, natural lighting, and local materials, which have proven to be effective in creating energy-efficient and sustainable buildings. Through literature analysis and case studies, this research demonstrates that the application of bioclimatic principles can reduce energy consumption and improve thermal comfort. The findings underscore the importance of climate considerations in architectural design, especially in tropical regions. This study concludes that bioclimatic design is not only relevant but also critical for the development of sustainable and climate-adaptive public facilities. Further research is needed to monitor long-term performance and apply it to other building types. This project provides a model that can be adapted for public facilities in other tropical regions, promoting more environmentally friendly design practices.